Effect of clay and lime nano-additives on the freeze–thaw durability of hot mix asphalt. Issue 3 (4th May 2017) - Akbari, Abbas; Modarres, Amir
Abstract : Durability of hot mix asphalt (HMA) against freeze–thaw cycles is mostly related to bitumen-aggregate adhesion. Improving the bonding quality between aggregates and bitumen would reduce the HMA moisture susceptibility and increase its durability. This study focused on the effects of nano-additives, including nano-clay (NC) and nano-lime (NL) on the durability of HMA. Limestone and granite aggregates were used to prepare the HMA specimens. Nano-additives were blended with 60/70 penetration grade bitumen at different rates, including 3%, 6%, and 9% by weight of bitumen. The mechanical properties of HMAs were determined using indirect tensile strength (ITS) and resilient modulus tests before and after one, three, and five freeze–thaw conditioning cycles. Afterwards, the moisture damage of mixes were evaluated using the surface free energy (SFE) concept. The SFEs of unmodified and modified bitumens were measured using the Wilhelmy plate test. Likewise, the SFEs of aggregates were evaluated by a universal sorption device procedure. Based on the results obtained, the addition of proper NC and NL content will enhance the tensile strength and resilient modulus ratios. The optimum NC and NL contents were determined as equal to 3% and 6%, respectively. The difference between the bitumen-aggregate and water-aggregate SFEs showed peak points, which were obtained at the optimum additive content. These peak points were mostly in accordance with the peak of ITS and resilient modulus tests before and after conditioning cycles.